(untitled) (Contemporary Central & East European Law, 2020)
In the Internet society, we are accustomed to the originators of creative works asserting strong protection of their output. Similarly, we witness extremely casual appropriation of works that is easier than ever to discover. Fashion products are an interesting case in this regard – through the relatively short history of the industry, protection of works has tended to be quite loose. Until recently, the consequences of copying in the fashion sector were not particularly serious, but the emergence of the connected society and the increased speed and scale of this copying threaten to cause more noticeable damage. The awareness that new threats call for a more serious approach to protection of creations requires examination of how and whether the familiar principles of copyright law can be applied to fashion designs and products, and to what extent. This paper outlines the background to such protections in the fashion industry, including examples of both strong and relaxed approaches by industry players. There is a brief presentation of case law that demonstrates how copyright principles can be applied to fashion, while also noting the role of society in applying the norms that determine the extent to which laws, once written, can actually be applied.